How is the State Perceived as Fair? A Literature Review of Social Identity-Based Procedural Justice in the National Context - Andina Mega Larasati; Joevarian Hudiyana; Hamdi Muluk (Faculty of Psychology Universitas Gadjah Mada, 2021)
Justice is relevant in various domains of life, including the state. The social identity-based procedural justice theories (Group Value Model and Group Engagement Model) emphasize the importance of procedural justice from the authority in signaling the group’s inclusion and respect, thus increasing individuals’ cooperation and compliance. This article aims to critically review published literature using the two models in a national context, of which there were inconsistent findings regarding the role of group identification. Three issues are underlying this inconsistency. First, both models could be applied when national identity was salient, such as legal compliance (to taxation and traffic law). Second, perceived police legitimacy is a better mediator when the national identity was not salient (e. g. cooperation in counter-terrorism and crowd policing). Third, the effect of procedural justice depends on the motivation to secure identity (which is generally higher among minority/marginalized groups). As both models are strongly bound by context, the author suggests controlling police-national identity prototypicality on studies about police procedural justice, attitude toward outgroup and relational identification with the police on studies involving intergroup conflict, and uncertainty about membership status on studies toward minority groups. Hopefully, this article could contribute references and encourage related studies in Indonesia.